Cybercartography for education: The application of cybercartography to teaching and learning in nunavut, canada - Taylor, D.R. (Fraser); Cowan, C. (Cindy); Ljubicic, G. (Gita); Sullivan, C. (Carmelle) (2014)
As outlined in Chapter 1, many of the characteristics of cybercartography lend themselves to improving teaching and learning in a variety of different settings. This chapter will examine the potential in both community college and high school settings in Nunavut, Canada. Education in Nunavut poses a number of challenges, especially the need to include traditional knowledge to increase the cultural relevance of the curriculum. The cybercartographic atlases being produced in cooperation with northern communities, such as the Inuit siku (sea ice) Atlas described in Chapter 14 and the earlier Arctic Bay Atlas (described in this Chapter), are making a valuable contribution to the educational challenges in both a formal and informal sense. This chapter begins by looking at the theoretical relevance of cybercartography to education using Howard Gardner's theories. This is followed by a consideration of the educational context in Nunavut, and the application of cybercartography in both Nunavut high schools (the Inuit siku (sea ice) Atlas) and Nunavut Arctic College (the Arctic Bay Atlas) contexts. In educational terms, the processes by which these atlases were created and the active involvement of Inuit communities are of equal, if not, greater, importance than the artefacts themselves.